Characterization of different solid fuels from waste for an advanced online fuel control system designed for large-scale incineration plants - Oischinger, Jürgen; Kohl, Markus; Meiller, Martin; Walberer, Julian; Daschner, Robert; Hornung, Andreas; Grafmans, Florian; Warnecke, Ragnar; Breitenberger, Robert; Dannerbeck, Franz; Zwiellehner, Martin (Waste Management & Research, 2023)
Despite many years of experience in the incineration of solid fuels from waste, the heterogeneity of solid fuels and their varying properties still pose a challenge for a stable and clean combustion in large-scale incineration plants. In modern facilities such as municipal waste incineration plants there still exists a lack of knowledge on the exact amount and calorific value of waste entering onto the grate. Based on the works of Warnecke et al. and Zwiellehner et al., in our project ‘AdOnFuelControl’, we determined the initial bulk density at the feed hopper by measuring the weight of the waste via the crane weigher and the volume via a high-performance 3D laser scanner. With the help of the determined bulk density, the lower heating value (LHV) and the compression in the feed hopper were calculated. All this information was integrated into the combustion control system, which provided a high potential for an optimized operation of the plant. In this article, six different fuels (fresh and aged municipal solid waste, refuse-derived fuel (fluff), refuse-derived fuel (fine grain), waste wood and dried, grained sewage sludge) were examined for the elemental composition, the LHV, fuel-specific parameters and the compression behaviour. In addition, initial tests with the 3D laser scanner as well as formulas for the calculation of the density in the feed hopper were presented. Based on the results of the experiments, the chosen approach seems very promising for optimized combustion control in large-scale incineration plants. As a next step, the gained knowledge and technology should be integrated in the municipal waste incineration plant.
CRIS-Team Scopus Importer:2023-07-07
Keywords: advanced online fuel control system; bulk density; fuels; large-scale incineration plants; laser; lower heating value (LHV); municipal solid waste incineration (MSWI); volume measurement; waste incineration